2016
DOI: 10.1177/1076029616679505
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of ACE I/D Polymorphisms Alone and With Concomitant Risk Factors on Coronary Artery Disease

Abstract: The ACE D allele may be predictive in individuals who may be at risk of developing CAD. Further investigations of these polymorphisms and their possible synergisms with traditional risk factors for CAD could help to ascertain better predictability for CAD susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 47 publications
2
33
0
1
Order By: Relevance
“…Previous studies have shown that ACE DD had close association with a high incidence of cardiovascular disease or endothelial dysfunction (Alvarez et al, 2001;Brand and van der Schouw, 2010;Kuzubova et al, 2013;Al-Hazzani et al, 2014;Amara et al, 2018). In the present study, only the result of pre-menopause group was consistent with previous studies, i.e., women of ACE DD had lower FMD than women of ACE DI/II, and in post-menopause group, women of the two ACE genotypes did not present significant difference in FMD.…”
Section: Ace D/i Polymorphism In Relation To Fmd Aging and Menopaussupporting
confidence: 90%
“…Previous studies have shown that ACE DD had close association with a high incidence of cardiovascular disease or endothelial dysfunction (Alvarez et al, 2001;Brand and van der Schouw, 2010;Kuzubova et al, 2013;Al-Hazzani et al, 2014;Amara et al, 2018). In the present study, only the result of pre-menopause group was consistent with previous studies, i.e., women of ACE DD had lower FMD than women of ACE DI/II, and in post-menopause group, women of the two ACE genotypes did not present significant difference in FMD.…”
Section: Ace D/i Polymorphism In Relation To Fmd Aging and Menopaussupporting
confidence: 90%
“…Mortality related to SARS-CoV-2 infections has been linked to various comorbid conditions such as hypertension, diabetes, hyperlipidemia, coronary artery disease, and renal disease [19] . High producer of ACE, the DD genotype has been associated with susceptibility to hypertension [20] , type 2 diabetes [21] , coronary artery disease [22] and hyperlipidemia [22] indicating a possible role of ACE I/D polymorphism with SARS-CoV-2 related mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Besides that, in a recently published study by the author (Falahati and Arazi, 2019), I/D genotype was associated neither with VO 2max nor with RHR and blood pressure. In contrast, in some other studies, patients with the DD genotype compared with the ID/II groups had higher (P < 0.05) NT-proBNP (Palmer et al, 2003) and a greater risk of coronary artery disease (Amara et al, 2018). The underlying reasons for the observed disagreements may be ethnic as well as geographic differences (Nakhjavani et al, 2007), using individuals with mixed heritage and none of Asian ethnicity (Albuquerque et al, 2014), choosing cardiac patients (Palmer et al, 2003), and age and sex difference.…”
Section: Discussionmentioning
confidence: 86%